Influence of plastic wake length on results of 3D numerical modelling of plasticity induced crack closure - Camas, D. (2019)
The numerical analysis of the plasticity induced crack closure requires the development of the plastic wake. Transient behaviour is observed when the crack starts to grow. The plastic wake length has an influence on the crack closure results and a great impact on the computational cost. Previous works have analysed the influence of this parameter considering bi-dimensional specimens in either plane strain or plane stress conditions. Lately, some three-dimensional models have appeared in order to analyse the crack closure phenomenon. The main scope of this study is to quantify and comprehend the minimum length required to stabilise the crack opening and closure values considering a three-dimensional model. On this purpose, a CT aluminium specimen has been modelled three-dimensionally considering a straight crack front and several calculations have been made in order to evaluate the influence of the simulated plastic wake. The numerical analysis is made in terms of crack closure and opening values.